Guidance in reading strategies: a first step towards autonomous learning in a semi-distance education program (2009)
This article aims at sharing the results of a research project focused on guiding students in the use of different reading strategies: reading non- text information, skimming and scanning, using contextual reference, predicting, and using true/false cognates as a first step towards autonomous learning. The project was conducted at a Colombian university with two groups of business administration students who belonged to a semi-distance education program. Informal talks with students, questionnaires, interviews and a teacher’s diary were used to collect the information in this action research study. Findings revealed that by knowing several reading strategies the students could reflect upon their learning; meta-cognition processes were enhanced and confidence for students to work by themselves was built up. Key words: Autonomous learning, distance education programs, reading strategies Este artículo discute los resultados de una investigación enfocada en guiar a los estudiantes en el uso de diferentes estrategias de lectura: información no textual, “skimming and scanning”, utilización de referentes contextuales, predicción y cognados, como un primer paso para promover el aprendizaje autónomo. Este estudio se realizó en una universidad colombiana con dos grupos de estudiantes pertenecientes al programa de administración de empresas a distancia. Para recolectar la información en este estudio de investigación acción, se emplearon conversaciones informales con los estudiantes, cuestionarios, entrevistas y el diario de campo del profesor. Los resultados mostraron que la exposición a diferentes estrategias de lectura promueve reflexión respecto al propio aprendizaje; se incrementaron procesos de metacognición y se generó confianza para trabajar autónomamente. Palabras clave: Aprendizaje autónomo, programas a distancia, estrategias de lectura